The Impact of Domestic Violence and Sexual Assault on Family Dynamics and Child Development: A Comprehensive Review - Matthias Brockstedt; Serpil Uğur Baysal; Kadir Daştan (Turkish Archives of Pediatrics)
This review synthesizes current research on domestic violence and sexual assault, focusing on their short-term and long-term effects on family dynamics, particularly on the development and well-being of children and adolescents. The article employs a curated body of literature, including surveys, reviews, program evaluations, and international health reports, to elucidate the direct and collateral damage caused by such trauma within families. The review critically examines the intersecting consequences of abuse, including immediate psychological distress and long-term socio-economic and educational disruptions for affected youths. Additionally, the review examines structural impediments and cultural intricacies that shape reporting practices and access to support services. The role of civil legal aid and victim advocacy in promoting survivor safety and justice is discussed, supported by findings from service evaluation studies. The review also addresses the exacerbating effects of the Coronavirus pandemic on domestic violence rates and service provision, noting increased occurrences of domestic abuse and decreased pursuit of urgent care and support, highlighting research conducted from the pandemic’s start through 2023. Emergent studies reveal a rise in domestic abuse occurrences and a decline in urgent care and support pursuit, emphasizing the need for adapted intervention strategies. The review offers evidence-based recommendations for policymakers, healthcare providers, and community organizations, stressing the necessity of persistent and collaborative efforts to address and prevent domestic violence. The ultimate goal is to advocate for a stronger international response to repair harm and prevent future occurrences, ensuring a safer environment for all family members, particularly children and adolescents.